Formulation of the Menu of a General Hospital After Its Conversion to a “COVID Hospital”: A Nutrient Analysis of 28-Day Menus - Detopoulou, Paraskevi; Al-Khelefawi, Zena Hardan; Kalonarchi, Garifallia; Papamikos, Vasilios (Frontiers in Nutrition, 2022)
Aim The aim of the present study was to modify the hospital menu to increase energy and protein provision in COVID-19 patients. Methods After the conversion of our hospital to a COVID-19 hospital, eggs, and comfort foods such as vanilla pudding were added to the menu to boost energy and protein intake of patients. All meals of the standard menu of the hospital, i.e., breakfast, lunch, and dinner were recorded for 14 consecutive days during two periods: pre-COVID-19 and after being converted to a “COVID hospital.” The menus were analyzed with the use of the USDA database. Results The total content of energy (1,873 ± 87 vs. 2,489 ± 137 Kcal), protein (97 ± 11 vs. 126.4 ± 18.7 g), fat (55 ± 9 vs. 74.1 ± 12.8 g), and carbohydrate (241.0 ± 16.0 vs. 323.0 ± 16.0 g) of the provided menus was increased in the COVID-19 period compared to the pre-COVID period. The leucine provision was also increased (4.8 ± 1.08 vs. 7.2 ± 1.3 g). Changes in protein and leucine were greater for breakfast (10 vs. 21 g protein and 0.8 vs. 1.7 g of leucine). The menu during COVID-29 provided more vitamin C (69.5 vs. 109.4 mg), thiamine (1.5 vs. 1.6 mg), riboflavin (2.1 vs. 2.6 mg), niacin (20.6 vs. 27.2 mg), pantothenic Acid (5.7 vs. 7.9 mg), vitamin B6 (2 vs. 2.6 mg), folate (274 vs. 334 μg), B12 (4.8 vs. 6.2 μg), choline (296 vs. 458 mg) as well as vitamins A (8,564 vs. 21,258 IU), D (3.9 vs. 4.7 μg), and K (59.3-111.5 μg). As far as micronutrients are concerned, the provisions of calcium (972 vs. 1375 mg), iron (10.2-12.8 mg), magnesium (236 vs. 294 mg), phosphorus (1,325 vs. 1,807 mg), copper (1.0 vs. 1.3 mg), manganese (2.1 vs. 2.4 mg) and selenium (148 vs. 183 μg) were increased during the COVID-19 period. Conclusion Simple menu changes and addition of comfort foods can substantially boost the nutrient content of a hospital diet, which in concert with provision of oral nutritional supplements could have an impact on patients’ nutritional status.